Study of Women's Health Across the Nation (SWAN), 1999-2001: Visit 03 Dataset - Sutton-Tyrrell, Kim ([Verlag nicht ermittelbar], 2011)
The Study of Women's Health Across the Nation (SWAN), is a multi-site longitudinal, epidemiologic study designed to examine the health of women during their middle years. The study examines the physical, biological, psychological, and social changes during this transitional period. The goal of SWAN's research is to help scientists, health care providers, and women learn how mid-life experiences affect health and quality of life during aging. The data include questions about doctor visits, medical conditions, medications, treatments, medical procedures, relationships, smoking, and menopause related information such as age at pre-, peri- and post-menopause, self-attitudes, feelings, and common physical problems associated with menopause. The study is co-sponsored by the National Institute on Aging (NIA), the National Institute of Nursing Research (NINR), the National Institutes of Health (NIH), and the NIH Office of Research on Women's Health. The study began in 1994. Between 1999 and 2001, 2,710 of the 3,302 women that joined SWAN were seen for their third follow-up visit. The research centers are located in the following communities: Ypsilanti and Inkster, MI (University of Michigan); Boston, MA (Massachusetts General Hospital); Chicago, IL (Rush Persbyterian-St. Luke's Medical Center); Alameda and Contra Costa County, CA (University of California-Davis, and Kaiser Permanente); Los Angeles, CA (University of California-Los Angeles); Hackensack, NJ (Hackensack University Medical Center); and Pittsburgh, PA (University of Pittsburgh). SWAN participants represent five racial/ethnic groups and a variety of backgrounds and cultures.